Randomized clinical trial on ivermectin versus thiabendazole for the treatment of strongyloidiasis. - Zeno Bisoffi; Dora Buonfrate; Andrea Angheben; Marina Boscolo; Mariella Anselmi; Stefania Marocco; Geraldo Monteiro; Maria Gobbo; Giulia Bisoffi; Federico Gobbi (Public Library of Science (PLoS), 2011)
BACKGROUND: Strongyloidiasis may cause a life-threatening disease in immunosuppressed patients. This can only be prevented by effective cure of chronic infections. Direct parasitologic exams are not sensitive enough to prove cure if negative. We used an indirect immune fluorescent antibody test (IFAT) along with direct methods for patient inclusion and efficacy assessment. METHODOLOGY/PRINCIPAL FINDINGS: Prospective, randomized, open label, phase III trial conducted at the Centre for Tropical Diseases (Verona, Italy) to compare efficacy and safety of ivermectin (single dose, 200 µg/kg) and thiabendazole (two daily doses of 25 mg/Kg for two days) to cure strongyloidiasis. The first patient was recruited on 6(th) December, 2004. Follow-up visit of the last patient was on 11(th) January, 2007. Consenting patients responding to inclusion criteria were randomly assigned to one of the treatment arms. Primary outcome was: negative direct and indirect (IFAT) tests at follow-up (4 to 6 months after treatment) or subjects with negative direct test and drop of two or more IFAT titers. Considering 198 patients who concluded follow-up, efficacy was 56.6% for ivermectin and 52.2% for thiabendazole (p = 0.53). If the analysis is restricted to 92 patients with IFAT titer 80 or more before treatment (virtually 100% specific), efficacy would be 68.1% for ivermectin and 68.9% for thiabendazole (p = 0.93). Considering direct parasitological diagnosis only, efficacy would be 85.7% for ivermectin and 94.6% for thiabendazole (p = 0.21). In ivermectin arm, mild to moderate side effects were observed in 24/115 patients (20.9%), versus 79/108 (73.1%) in thiabendazole arm (p = 0.00). CONCLUSION: No significant difference in efficacy was observed, while side effects were far more frequent in thiabendazole arm. Ivermectin is the drug of choice, but efficacy of single dose is suboptimal. Different dose schedules should be assessed by future, larger studies. TRIAL REGISTRATION: Portal of Clinical Research with Medicines in Italy 2004-004693-87